2017
DOI: 10.1177/1971400916687584
|View full text |Cite
|
Sign up to set email alerts
|

Extra-axial ependymoma of the cerebral convexity: A very rare intracranial adult tumor

Abstract: Background Ependymomas are rare adult tumors that originate from the ventricular system or the ependymal surface of the central canal. Extra-axial supratentorial ependymomas are extremely rare, and only five cases have been reported to date in the English literature. Case presentation A 46-year-old previously healthy male presented with a gradual painless loss of vision in the right eye. Cerebral MRI showed a right parietal-occipital lesion resembling an atypical meningioma. Surgical resection was performed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…reported in 2017 that there were only 14 adult cases in the English literature of intracranial extra-axial ependymomas. [ 3 ] Although ependymomas may extend into the CPA or subarachnoid space, a primary extra-axial intracranial ependymoma in the CPA is extremely rare. [ 8 ] Ebrahimi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported in 2017 that there were only 14 adult cases in the English literature of intracranial extra-axial ependymomas. [ 3 ] Although ependymomas may extend into the CPA or subarachnoid space, a primary extra-axial intracranial ependymoma in the CPA is extremely rare. [ 8 ] Ebrahimi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[15] Berhili et al reported in 2017 that there were only 14 adult cases in the English literature of intracranial extra-axial ependymomas. [3] Although ependymomas may extend into the CPA or subarachnoid space, a primary extra-axial intracranial ependymoma in the CPA is extremely rare. [8] Ebrahimi et al highlighted the importance of considering ependymomas as a differential diagnosis among CPA tumors as six adult cases of CPA ependymomas had been reported in the English literature by 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In the radiologic findings of this case, pure cortical type, absence of a cystic lesion, and with no connection to ventricle were factors that contributed to the difficulty in recognizing the tumor as an EPN. Because a pure cortical, extra-ventricular nature, and with no ventricular lining are rare findings in EPNs [ 5 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only few case reports on extraaxial ependymomas exist (IEAE). Due to the rare entity of IEAE, no precise relation to intra-axial ependymomas can be made, but the vast majority are intra-axial lesions (34)(35)(36).…”
Section: Ependymomamentioning
confidence: 99%